MODEL LAYANAN PUBLIK RAMAH DIFABEL INISIATIF MEMBANGUN KOTA INKLUSI: Diffabble-Friendly Public Service Model Building Initiatives the City of Inclusion - Rahmawati; Heru Adi Putranto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Disability is a complex issue at all levels of society. Disabilities include people with physical and psychological deficiencies in society. So the mention of people with disabilities can be more familiar by calling them disabled. With the diffable predicate, people can easily divide their social strata with 'normal people' rather than 'disabled/disabled people'. The purpose of this research is to find ideas and theoretical foundations that can be used to define